2020
DOI: 10.3340/jkns.2020.0013
|View full text |Cite
|
Sign up to set email alerts
|

Change of Pyogenic and Tuberculous Spondylitis between 2007 and 2016 Year : A Nationwide Study

Abstract: Objective We attempted to compare the incidence of pyogenic spondylitis (PS) and tuberculous spondylitis (TS) between 2007 and 2016. Furthermore, we investigated the patients who underwent surgery in 2016 compared to that in 2007. Methods We used a nationwide database managed by the Korean National Health Insurance Service (NHIS) in 2007 and 2016. Total 9655 patients with a newly diagnosis of PS or TS were enrolled in PS or TS group. Among them, 1721 patients underwent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 32 publications
(51 reference statements)
0
16
0
Order By: Relevance
“…The microorganisms reach the vertebra through hematogenous spread or during a spinal surgery, procedure, or directly from a site close to the vertebra. Microorganisms known to cause infectious spondylitis are diverse, with regional and periodic variation in distribution [ 3 7 ]. The most common species causing infectious spondylitis in Korea are bacteria and Mycobacterium tuberculosis .…”
Section: Etiologic Microorganismsmentioning
confidence: 99%
See 1 more Smart Citation
“…The microorganisms reach the vertebra through hematogenous spread or during a spinal surgery, procedure, or directly from a site close to the vertebra. Microorganisms known to cause infectious spondylitis are diverse, with regional and periodic variation in distribution [ 3 7 ]. The most common species causing infectious spondylitis in Korea are bacteria and Mycobacterium tuberculosis .…”
Section: Etiologic Microorganismsmentioning
confidence: 99%
“…The most common species causing infectious spondylitis in Korea are bacteria and Mycobacterium tuberculosis . Recently, the incidence of pyogenic spondylitis has increased, whereas the incidence of tuberculous spondylitis has decreased [ 7 ]. Brucella is a common etiologic microorganism of infectious spondylitis in the Mediterranean, Middle East, Latin America and West Asia, but it is rare in Korea [ 8 9 ] with a very low incidence of spondylitis caused by non-tuberculous mycobacteria or fungi [ 10 11 12 ].…”
Section: Etiologic Microorganismsmentioning
confidence: 99%
“…Our study also showed that PS was associated with an increased prevalence of diabetes mellitus. The reported incidences of PS are increasing due to increased life expectancy; the popularity of spinal, percutaneous invasive interventions; and advanced diagnostic methods [1,[13][14][15][16]. In cases of hematogenous spreading pathogens in PS, Staphylococcus aureus is the predominant pathogen, accounting for half of non-tuberculous cases [17][18][19].…”
Section: Discussionmentioning
confidence: 99%
“…Pyogenic spondylitis is an infrequent infection of the spine that arises via a hematogenous route and is most often reported in immunocompromised patients. A recent nationwide study (1) showed a greater increase in pyogenic spondylitis cases than in tuberculous spondylitis cases.…”
Section: Introductionmentioning
confidence: 95%